2006
DOI: 10.1093/ajcn/83.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of metabolic abnormalities in adolescents with the hypertriglyceridemic waist phenotype

Abstract: Background: It remains unknown whether the hypertriglyceridemic waist (HW) phenotype, an appropriate screening tool in adults, can also be used to screen for metabolic abnormalities in adolescents. Objective: We aimed to evaluate metabolic risk factors identified by the HW phenotype in adolescents. Design: Anthropometric and biochemical measurements were assessed in a population-based cross-sectional study of 1413 male and 1623 female Iranian adolescents aged 10 -19 y. The HW phenotype was defined as serum tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
71
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 46 publications
15
71
2
3
Order By: Relevance
“…He was therefore clearly abdominally obese. Because his previous lipid profile indicated that he had hypertriglyceridemia, he was therefore diagnosed at the Quebec Heart Institute as having the 'hypertriglyceridemic waist' phenotype, which has been shown to be predictive of the likely presence of a cluster of atherogenic and diabetogenic abnormalities often referred to as the metabolic syndrome (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The objective of the present article is not to review the literature on the risk of cardiovascular disease (CVD) associated with abdominal obesity and the metabolic syndrome, because numerous review papers are already available on the topic (18)(19)(20)(21)(22).…”
Section: Evaluating Cad Risk On the Basis Of 'Traditional' Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…He was therefore clearly abdominally obese. Because his previous lipid profile indicated that he had hypertriglyceridemia, he was therefore diagnosed at the Quebec Heart Institute as having the 'hypertriglyceridemic waist' phenotype, which has been shown to be predictive of the likely presence of a cluster of atherogenic and diabetogenic abnormalities often referred to as the metabolic syndrome (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The objective of the present article is not to review the literature on the risk of cardiovascular disease (CVD) associated with abdominal obesity and the metabolic syndrome, because numerous review papers are already available on the topic (18)(19)(20)(21)(22).…”
Section: Evaluating Cad Risk On the Basis Of 'Traditional' Risk Factorsmentioning
confidence: 99%
“…Since the publication of our paper (2) describing for the first time the hypertriglyceridemic waist concept, more than 15 studies worldwide have examined the contribution of this simple screening phenotype in the identification of individuals likely to have features of the metabolic syndrome or reporting associations with type 2 diabetes and CAD (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Although slightly different cutoff values for waist circumference and triglyceride levels have been used across studies, essentially similar conclusions have been reached.…”
Section: The Hypertriglyceridemic Waist Phenotypementioning
confidence: 99%
“…In such cases, WC was approximated at the lateral level of the 12 th rib or lower floating rib. [23][24][25][26] These are well established and validated methods for assessment of hip circumference and WC and are used in several large scale studies. 27 Bioelectrical impedance was done using the Quantum II Bioelectrical Body Composition Analyzer (RJL Systems, Clinton Township, MI).…”
Section: Measurement Of Body Fat and Fat Distribution Indicesmentioning
confidence: 99%
“…In order to be able to readily identify those children who are most at risk of developing this disorder a simple and effective screening tool is required, and the WC appears to best fit the requirements of such a tool. While it is generally agreed that obesity is the predominant correlate of risk for MS among the young (Goodman et al 2005), an increasing number of studies are showing that WC is the best measure for identifying children with insulin resistance and hypertriacylglycerolaemia, and hence those most at risk for MS (Moreno et al 2002;Hirschler et al 2005;Esmaillzadeh et al 2006). WC has been found to perform better than BMI in this context, and these studies have recommended that WC should be used in paediatric clinical settings.…”
Section: Abdominal Fatness Ethnicity and Health Riskmentioning
confidence: 99%